An energy efficient cycle stealing algorithm for best effort services in wireless sensor networks. (1st January 2014) - Chauhan, Siddhartha; Awasthi, Lalit Kumar
Wireless sensor networks (WSNs) are resource constrained networks that have wide variety of applications. Quality of service (QoS) requirement differs for different applications of WSNs. Most of the energy consumed by the nodes is for transmission and reception of the packets. Reducing the transmission of data packets reduces the energy consumption of nodes. In this paper, we have proposed two energy efficient protocols for data reporting in WSNs. The proposed protocols namely cycle stealing algorithm (CSA) and energy efficient cycle stealing algorithm (EECSA) have been designed for nodes having two sensors, capable of sensing two different parameters. CSA and EECSA have been designed to efficiently handle two different types of data generated, with varying QoS requirements. Nodes can be fine-tuned according to specific requirements of applications by specifying acceptable limit which greatly affects the transmission of new data packets. The proposed protocols steal transmission cycles of rate guaranteed services in order to push data packets of best effort service. Simulation results show that proposed protocols are capable of handling redundant (similar) data by reducing the transmission of similar data packets thus conserving energy.